Gas diffusion layer with hydrophilic and hydrophobic transmission channel and preparation method thereof

By mixing and modifying carbon nanomaterials in the gas diffusion layer, forming a structure with a hydrophilic transmission channel, the problem of insufficient water management capabilities of the gas diffusion layer in the prior art at high current density is solved, and the performance of the device is significantly improved and stability.

CN119406727AActive Publication Date: 2025-02-11WUHAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411460931.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-11
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing gas diffusion layer cannot effectively manage moisture at high current density, resulting in a degradation in the performance of electrochemical devices under high operating sites and high humidity conditions.

Method used

By mixing the first carbon nanomaterial and the second carbon nanomaterial, hydrophilic and hydrophobic modifications are performed respectively to form a gas diffusion layer with a hydrophilic transport channel. During the preparation of microporous layer, the pores formed by large-particle carbon nanoparticles and the pores stacked by small particles are optimized to optimize drainage and oxygen transport capabilities.

Benefits of technology

It significantly improves the water management capability and oxygen transmission efficiency of the gas diffusion layer under high current density, reduces the flooding risk of the catalytic layer, and improves the performance and stability of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406727A_ABST
    Figure CN119406727A_ABST
Patent Text Reader

Abstract

The invention provides a gas diffusion layer with hydrophilic and hydrophobic transmission channels and a preparation method of the gas diffusion layer, and belongs to the technical field of hydrogen energy and hydrogen-rich fuel conversion. The preparation method of the gas diffusion layer comprises the following steps: mixing a first carbon nanomaterial, a hydrophilic modified first carbon nanomaterial, a second carbon nanomaterial and a hydrophobic modified second carbon nanomaterial to form a carbon material mixture; the particle size of the first carbon nanomaterial is larger than that of the second carbon nanomaterial; mixing the carbon material mixture, a solvent and a water repellent agent to form slurry; and forming a coating on a substrate by using the slurry, drying and sintering. The preparation method can improve the performance of the gas diffusion layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen energy and hydrogen-rich fuel conversion. Background Art

[0002] Hydrogen energy is a clean, renewable form of energy that is widely used in transportation, power generation and industry. The electrochemical production of green hydrogen from hydrogen-rich fuel and the application of green hydrogen are important ways to achieve carbon peak and carbon neutrality, and are of great significance in leading global climate governance.

[0003] Gas diffusion layer (GDL) is a core component for the conversion of hydrogen-rich fuels, hydrogen purification and efficient application of hydrogen energy. It plays an important role in the rapid transmission of water vapor, conduction of electrons and dispersion of mechanical applications. The material and structural properties of GDL (such as porosity, conductivity and corrosion resistance) directly affect the performance and efficiency of electrochemical devices, so the structural design and optimization of GDL is crucial.

[0004] The gas diffusion layer is mainly composed of a microporous layer (MPL) formed by stacking carbon particles and a matrix layer of stacked carbon fibers or carbon cloth. The conventional preparation method of existing MPL is wet coating preparation, firstly using water or a mixture of water and alcohol as a solvent, uniformly mixing carbon powder and polytetrafluoroethylene (PTFE) emulsion in a certain proportion to make it into a slurry with a certain viscosity, then coating it on the surface of the carbon matrix layer, and finally undergoing high-temperature sintering treatment.

[0005] With the optimization of key component materials and structures, electrochemical devices tend to operate at higher current densities, which also means that the rate of water produced by electrochemical reactions is higher, bringing new challenges to the water management of batteries. Water management has become one of the key factors limiting further performance improvements. The current commercial gas diffusion layer (GDL) preparation methods cannot meet the functional requirements of the material in the application scenario. Although some new experimental preparation methods can improve some performance, the preparation process is complex, and the processing and assembly precision requirements are high. It is also impossible to achieve the device working at an ultra-high working position, thereby improving the efficiency of the electrochemical device.

[0006] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0007] In view of this, the present invention proposes a gas diffusion layer with hydrophilic and hydrophobic transmission channels and a preparation method thereof, which can improve the water management ability of the gas diffusion layer under high current density and enhance the performance of the gas diffusion layer.

[0008] The technical solution of the present invention is achieved in this way:

[0009] The present invention provides a method for preparing a gas diffusion layer, comprising:

[0010] Step S1, mixing a first carbon nanomaterial, a hydrophilically modified first carbon nanomaterial, a second carbon nanomaterial, and a hydrophobically modified second carbon nanomaterial to form a carbon material mixture; the particle size of the first carbon nanomaterial is larger than the particle size of the second carbon nanomaterial;

[0011] Step S2, mixing the carbon material mixture, the solvent, and the hydrophobic agent to form a slurry;

[0012] Step S3, forming a coating on the substrate with the slurry, drying and sintering.

[0013] On the basis of the above technical solution, preferably, the particle size of the first carbon nanomaterial is 30 to 50 nm; and the particle size of the second carbon nanomaterial is 20 to 40 nm.

[0014] On the basis of the above technical solution, preferably, the mass percentage of the hydrophilically modified first carbon nanomaterial in the carbon material mixture is 15% to 30%, and the mass percentage of the hydrophobically modified second carbon nanomaterial in the carbon material mixture is 5% to 10%. On the basis of the above technical solution, preferably, the hydrophilically modified first carbon nanomaterial is prepared by the following method:

[0015] Step S101, dispersing the first carbon nanomaterial in deionized water to obtain a first carbon nanomaterial dispersion;

[0016] Step S102, adding p-phenylenediamine or p-aminobenzenesulfonic acid and nitric acid to the first carbon nanomaterial dispersion; ultrasonically stirring for 1 to 3 hours to obtain a first carbon nanomaterial pretreatment solution;

[0017] Step S103, adding nitrate to the first carbon nanomaterial pretreatment solution, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophilically modified first carbon nanomaterial.

[0018] Based on the above technical solution, preferably, in step S102, the mass ratio of p-phenylenediamine to the first carbon nanomaterial is (0.5-1):1000;

[0019] In step S103, a sodium nitrate aqueous solution is added dropwise to the first carbon nanomaterial pretreatment solution, and then reacted at 50 to 80°C for 10 to 14 hours.

[0020] On the basis of the above technical solution, preferably, the hydrophobically modified second carbon nanomaterial is prepared by the following method:

[0021] Step S201, dispersing the second carbon nanomaterial in a mixed solution of pentafluoroaniline and acetonitrile to obtain a second carbon nanomaterial dispersion;

[0022] Step S202, adding nitrite to the second carbon nanomaterial dispersion, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophobically modified second carbon nanomaterial.

[0023] On the basis of the above technical solution, preferably, in step S201, the second carbon nanomaterial is dispersed in a mixed solution of pentafluoroaniline and acetonitrile, and stirred for 1 to 3 hours under ultrasonic conditions to obtain a second carbon nanomaterial dispersion; wherein the mass of the second carbon nanomaterial: the mass of pentafluoroaniline = 1: (3 to 5);

[0024] In step S202, amyl nitrite is added to the second carbon nanomaterial dispersion, and then reacted under reflux conditions for 8 to 12 hours; wherein the working concentration of the amyl nitrite is 0.5 to 5 mol / L.

[0025] Based on the above technical solution, preferably, the first carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder; the second carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder.

[0026] On the basis of the above technical scheme, preferably, in step S2, the solvent is a mixed solvent of water and alcohol; the hydrophobic agent is at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-ethylene copolymer, and polyvinylidene fluoride.

[0027] The present invention also provides a gas diffusion layer, which is prepared by the above-mentioned preparation method.

[0028] The gas diffusion layer and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0029] Based on the surface affinity and size effect of carbon materials, this patent proposes a gas diffusion layer with hydrophilic and hydrophobic transmission channels. During the preparation of the microporous layer, the pores formed by large carbon nanoparticles are larger, while the pores formed by small stacked particles are smaller. Based on this principle and the need for high drainage of the gas diffusion layer, hydrophilic modification is performed on large carbon particles and hydrophobic modification is performed on the surface of small carbon particles to form a gas diffusion layer with hydrophilic and hydrophobic transmission channels. The embodiment and the comparative example are assembled into batteries for performance testing. In the higher current density area, at 2A / cm 2 The output performance of the embodiment is improved by 20% compared with the comparative example.

[0030] The hydrophilic modified first carbon nanomaterial can form a hydrophilic channel after sintering, thereby improving the drainage capacity of the gas diffusion layer and reducing the risk of flooding of the catalyst layer. The hydrophobic modified second carbon nanomaterial can form a hydrophobic channel after sintering, thereby facilitating oxygen transmission and improving efficiency.

[0031] In addition, the particle size of the first carbon nanomaterial is larger than that of the second carbon nanomaterial, which makes the size of the hydrophilic channel formed by the hydrophilically modified first carbon nanomaterial after sintering larger than the size of the hydrophobic channel formed by the hydrophobically modified second carbon nanomaterial after sintering, so that the drainage capacity and oxygen transport capacity of the gas diffusion layer are roughly balanced, making the performance of the gas diffusion layer better. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 S2p spectrum of the XPS analysis of the hydrophilically modified first carbon nanomaterial.

[0034] Figure 2 This is a contact angle analysis diagram of the hydrophilically modified first carbon nanomaterial.

[0035] Figure 3 F1s spectrum of XPS analysis of the hydrophobically modified second carbon nanomaterial.

[0036] Figure 4 This is a contact angle analysis diagram for the hydrophobically modified second carbon nanomaterial.

[0037] Figure 5 This is the polarization curve test result diagram. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In the prior art, the gas diffusion layer (GDL) is formed by directly mixing and coating a hydrophobic agent, a solvent, and carbon powder. At present, the aspects of optimizing the structure and performance of the GDL mainly include the porosity design of the microporous layer, the graded porosity of the microporous layer, the perforated structure of the microporous layer, resin binders with different hydrophilic and hydrophobic degrees, and composite gas diffusion layers prepared from different carbon powders. However, the above-mentioned improvement scheme does not fully consider the requirements of the electrochemical device for rapid water vapor transmission of the electrode under high current density, making the device prone to water flooding at high working points and high humidity conditions, and performance degradation. Based on this, the present invention provides a method for preparing a gas diffusion layer, comprising:

[0040] Step S1, mixing a first carbon nanomaterial, a hydrophilically modified first carbon nanomaterial, a second carbon nanomaterial, and a hydrophobically modified second carbon nanomaterial to form a carbon material mixture; the particle size of the first carbon nanomaterial is larger than the particle size of the second carbon nanomaterial;

[0041] Step S2, mixing the carbon material mixture, the solvent, and the hydrophobic agent to form a slurry;

[0042] Step S3, forming a coating on the substrate with the slurry, drying and sintering.

[0043] The slurry used in the gas diffusion layer provided by the invention contains a variety of carbon nanomaterials. The hydrophilically modified first carbon nanomaterial can form a hydrophilic channel after sintering, which is beneficial to improving the drainage capacity of the gas diffusion layer and reducing the risk of flooding of the catalyst layer. The hydrophobically modified second carbon nanomaterial can form a hydrophobic channel after sintering, which is beneficial to oxygen transmission and improves efficiency. In addition, the particle size of the first carbon nanomaterial is larger than that of the second carbon nanomaterial, which makes the size of the hydrophilic channel formed by the hydrophilically modified first carbon nanomaterial after sintering larger than the size of the hydrophobic channel formed by the hydrophobically modified second carbon nanomaterial after sintering, so that the drainage capacity and oxygen delivery capacity of the gas diffusion layer are roughly balanced, so that the performance of the gas diffusion layer is better. In other words, the present invention can make the gas diffusion layer maintain a high oxygen delivery capacity under the premise of having a high hydrophobic capacity by optimizing the type, size and performance of the carbon nanomaterials in the slurry, which is beneficial to improving performance. Thus, the present disclosure provides a method for preparing a gas diffusion layer with hydrophilic and hydrophobic transmission channels based on the surface affinity regulation and size effect of carbon materials, in response to the high power output operation requirements of existing gas diffusion layers under high working point operation and high gas humidification conditions. Hydrophilic channels are constructed while ensuring rapid gas diffusion. This method effectively improves the drainage management capability of the gas diffusion layer, reduces the risk of electrode flooding failure, and improves the performance and stability of electrochemical devices under high current density and high power output.

[0044] In one embodiment of the present disclosure, the particle size of the first carbon nanomaterial is between 30 and 50 nm; the particle size of the second carbon nanomaterial is between 20 and 40 nm. As an example, the particle size of the first carbon nanomaterial is 1.2 to 1.5 times that of the second carbon nanomaterial.

[0045] For example, the average particle size of the first carbon nanomaterial is 50 nm; and the average particle size of the second carbon nanomaterial is 35 nm.

[0046] In the disclosed embodiment, the hydrophilically modified first carbon nanomaterial is obtained by hydrophilically modifying the first carbon nanomaterial; and the hydrophobically modified second carbon nanomaterial is obtained by hydrophilically modifying the second carbon nanomaterial. Furthermore, the modification of the first carbon nanomaterial and the second carbon nanomaterial is carried out by inorganic substances or low molecular weight organic substances, for example, the surface of the carbon nanomaterial is modified by inorganic substances or small molecule organic substances. Therefore, the particle size of the hydrophilically modified first carbon nanomaterial is substantially consistent with the particle size of the first carbon nanomaterial; and the particle size of the hydrophobically modified second carbon nanomaterial is substantially consistent with the particle size of the second carbon nanomaterial. Thus, the particle size of the hydrophobically modified second carbon nanomaterial is smaller than the particle size of the hydrophilically modified first carbon nanomaterial.

[0047] In one embodiment of the present disclosure, the hydrophilically modified first carbon nanomaterial is prepared by the following method:

[0048] Step S101, dispersing the first carbon nanomaterial in deionized water to obtain a first carbon nanomaterial dispersion;

[0049] Step S102, adding p-phenylenediamine or p-aminobenzenesulfonic acid and nitric acid to the first carbon nanomaterial dispersion; ultrasonically stirring for 1 to 3 hours to obtain a first carbon nanomaterial pretreatment solution;

[0050] Step S103, adding nitrate to the first carbon nanomaterial pretreatment solution, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophilically modified first carbon nanomaterial.

[0051] Optionally, in step S102, the mass ratio of p-phenylenediamine to the first carbon nanomaterial is (0.5-1):1000.

[0052] Optionally, in step S101, before dispersing the first carbon nanomaterial in deionized water, the first carbon nanomaterial may be dried to accurately determine the amount of the first carbon nanomaterial. In one example, the first carbon nanomaterial is dried at 100° C. for 10 hours.

[0053] Optionally, in step S103, a sodium nitrate aqueous solution is added dropwise to the first carbon nanomaterial pretreatment solution, and then reacted at 50 to 80° C. for 10 to 14 hours.

[0054] Optionally, in step S103, after the reaction is completed, the hydrophilically modified first carbon nanomaterial is dried at 100°C for 10 hours after filtering and washing for multiple times.

[0055] In one embodiment of the present disclosure, the mass percentage of the hydrophilically modified first carbon nanomaterial in the carbon material mixture is 15% to 30%, and the mass percentage of the hydrophobically modified second carbon nanomaterial in the carbon material mixture is 5% to 10%. The mass percentage of the first carbon nanomaterial in the carbon material mixture is 20% to 35%, and the mass percentage of the second carbon nanomaterial in the carbon material mixture is 40% to 45%.

[0056] In one embodiment of the present disclosure, the hydrophobically modified second carbon nanomaterial is prepared by the following method:

[0057] Step S201, dispersing the second carbon nanomaterial in a mixed solution of pentafluoroaniline and acetonitrile to obtain a second carbon nanomaterial dispersion;

[0058] Step S202, adding nitrite to the second carbon nanomaterial dispersion, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophobically modified second carbon nanomaterial.

[0059] Optionally, in step S201, the second carbon nanomaterial is dispersed in a mixed solution of pentafluoroaniline and acetonitrile, and stirred for 1 to 3 hours under ultrasonic conditions to obtain a second carbon nanomaterial dispersion; wherein the mass of the second carbon nanomaterial: the mass of pentafluoroaniline = 1: (3 to 5).

[0060] Optionally, in step S201, the ratio of the second carbon nanomaterial to acetonitrile is between 1 g: (100 mL to 200 mL).

[0061] Optionally, in step S201, before dispersing the second carbon nanomaterial in the mixed solution of pentafluoroaniline and acetonitrile, the second carbon nanomaterial may be dried to accurately determine the amount of the second carbon nanomaterial. In one example, the first carbon nanomaterial is dried at 100° C. for 10 hours.

[0062] Optionally, in step S202, amyl nitrite is added to the second carbon nanomaterial dispersion, and then reacted under reflux conditions for 8 to 12 hours; wherein the working concentration of the amyl nitrite is 0.5 to 5 mol / L.

[0063] Optionally, in step S202, after the reaction is completed, the hydrophobically modified second carbon nanomaterial is dried at 100°C for 10 hours after filtering and washing for multiple times.

[0064] In one embodiment of the present disclosure, the first carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder; the second carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder. The first carbon nanomaterial and the second carbon nanomaterial can be the same material but have different particle sizes. Of course, the first carbon nanomaterial and the second carbon nanomaterial can also be different.

[0065] In one example, the first carbon nanomaterial is selected from acetylene black powder.

[0066] In one example, the second carbon nanomaterial is selected from Vulcan-XC72.

[0067] In one embodiment of the present disclosure, in step S2, the carbon material mixture may be dispersed in a mixed solvent consisting of water and alcohol to obtain a carbon material mixture dispersion, for example, dispersed in a mixed solvent consisting of water and isopropanol, and then a hydrophobic agent is added to the carbon material mixture dispersion and mixed to form a slurry.

[0068] Furthermore, the mass ratio of the carbon material mixture to the carbon material mixture dispersion is (5-15):100.

[0069] Optionally, when the carbon material mixture is dispersed in a mixed solvent consisting of water and alcohol, the carbon material mixture dispersion may be treated under ultrasound for 20 to 40 minutes to ensure that the carbon material mixture is fully dispersed.

[0070] Optionally, when a hydrophobic agent is added to the carbon material mixture dispersion, the hydrophobic agent is at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-ethylene copolymer, and polyvinylidene fluoride. Further, the mass ratio of the hydrophobic agent to the mass of the carbon material mixture is (2-6):10.

[0071] In one example, PTFE (polytetrafluoroethylene) emulsion can be added to the carbon material mixture dispersion and stirred for 20 to 40 minutes to achieve full mixing of the carbon material and the hydrophobic agent.

[0072] In one embodiment of the present disclosure, in step S3, a coating is formed on a substrate using the slurry, and then dried and sintered.

[0073] In one example, the substrate may be carbon paper. Of course, other substrate materials may also be selected as needed.

[0074] Optionally, a coating machine may be used to coat the slurry on the substrate to form a coating layer, and the coating layer thickness may be between 30 and 100 microns, such as 50 microns.

[0075] Optionally, the coated substrate can be placed in a 90°C oven to dry for 20 to 40 minutes, then dried at a high temperature (e.g., 230 to 280°C) in a tubular furnace for 20 to 40 minutes, and finally sintered at 350°C in a tubular furnace for 20 to 40 minutes to obtain the desired gas diffusion layer.

[0076] As follows, the method for preparing the gas diffusion layer of the present invention is exemplarily described in combination with a plurality of specific embodiments.

[0077] Example 1

[0078] Step S1:

[0079] Acetylene black is used as the first carbon nanomaterial, and the particle size is 50 nm.

[0080] Dry acetylene black at 100°C for 10 hours; then place 4g of dried acetylene black, 2.6mg of p-aminobenzenesulfonic acid and 10uL of nitric acid in a flask and ultrasonically stir for 2 hours to obtain the first carbon nanomaterial pretreatment solution; take 2.4g of sodium nitrate and dissolve it in 10mL of deionized water, and then add it dropwise to the above-mentioned first carbon nanomaterial pretreatment solution; react at 70°C for 12 hours; filter and wash the product several times and dry it at 100°C for 10 hours to obtain the hydrophilically modified first carbon nanomaterial. The hydrophilically modified first carbon nanomaterial was analyzed by XPS (X-ray photoelectron spectroscopy), and its S2p ​​spectrum is as follows Figure 1 As shown. Figure 1 The hydrophilically modified first carbon nanomaterial contains sulfur, which indicates that it is modified by p-aminobenzenesulfonic acid, thereby making it hydrophilic. The contact angle of the hydrophilically modified first carbon nanomaterial is analyzed. Figure 2 As shown. Figure 2 The contact angle of the hydrophilically modified first carbon nanomaterial is 106.5°. This surface shows that the hydrophobicity of the hydrophilically modified first carbon nanomaterial is significantly weakened by modifying the first carbon nanomaterial.

[0081] The second carbon nanomaterial is Vulcan-XC72, and the particle size is 35 nm.

[0082] The second carbon nanomaterial was dried at 100°C for 10 hours. Then, 1g Vulcan-XC72, 4g pentafluorophenyl, and 150mL acetonitrile were added to the flask, and mixed and ultrasonically stirred for 2 hours under a nitrogen atmosphere to obtain a second carbon nanomaterial dispersion; then 3.7mL amyl nitrite was gradually added and heated to reflux for 10 hours; after filtering and washing several times, the sample was dried at 100°C for 10 hours to obtain a hydrophobically modified second carbon nanomaterial. The hydrophobically modified second carbon nanomaterial was subjected to XPS (X-ray photoelectron spectroscopy) analysis, and its F1s spectrum was as follows Figure 3 As shown. Figure 3 The hydrophobically modified second carbon nanomaterial contains fluorine, which indicates that it is modified by pentafluorophenyl, thus making it hydrophobic. The contact angle of the hydrophobically modified second carbon nanomaterial is analyzed. Figure 4 As shown. Figure 4 The contact angle of the hydrophobically modified second carbon nanomaterial is 142.7°. This surface shows that the hydrophobicity of the hydrophobically modified second carbon nanomaterial is significantly improved by modifying the second carbon nanomaterial.

[0083] The first carbon nanomaterial, the hydrophilically modified first carbon nanomaterial, the second carbon nanomaterial, and the hydrophobically modified second carbon nanomaterial are mixed to form a carbon material mixture. The mass proportion of the hydrophilically modified first carbon nanomaterial is 30%; the mass proportion of the hydrophobically modified second carbon nanomaterial is 5%. The mass proportion of the first carbon nanomaterial is 20%, and the mass proportion of the second carbon nanomaterial is 45%.

[0084] Step S2:

[0085] The carbon material mixture was dissolved in a mixed solvent of water and isopropanol and stirred for 30 minutes to obtain a carbon material mixture dispersion; the mass of the carbon material mixture / the mass of the carbon material mixture dispersion was 8%; and the volume ratio of water to isopropanol was 1:3.

[0086] PTFE (polytetrafluoroethylene) emulsion was added to the above carbon material mixture dispersion and stirred for 30 minutes to obtain slurry; wherein the mass of PTFE / the mass of carbon material mixture was 40%.

[0087] Step S3:

[0088] Using a coating machine, the slurry is coated on the carbon paper with a thickness of 50 μm to obtain a coating;

[0089] The prepared coating was first dried in an oven at 90°C for 30 min, then dried in a tubular furnace at 250°C for 30 min, and finally sintered at 350°C for 30 min to obtain a gas diffusion layer capable of efficient water management, which is marked as gas diffusion layer A1 in the present invention.

[0090] Embodiment 2:

[0091] The gas diffusion layer was prepared by a method substantially the same as that in Example 1; the difference between the preparation process and that in Example 1 was that the mass ratio of the hydrophilically modified first carbon nanomaterial in the carbon material mixture was 15%, and the mass ratio of the hydrophobically modified second carbon nanomaterial in the carbon material mixture was 10%. The mass ratio of the first carbon nanomaterial was 35%, and the mass ratio of the second carbon nanomaterial was 40%.

[0092] The gas diffusion layer obtained in this embodiment is marked as gas diffusion layer A2 in the present invention.

[0093] Comparative Example 1:

[0094] The gas diffusion layer was prepared by a method substantially the same as that in Example 1; the difference between the preparation process and Example 1 was that the first carbon nanomaterial was not subjected to hydrophilic modification, and the second carbon nanomaterial was not subjected to hydrophobic modification. The amount of the first carbon nanomaterial in the slurry of Comparative Example 1 was equal to the total amount of the first carbon nanomaterial and the hydrophilically modified first carbon nanomaterial in the slurry of Example 1. The amount of the second carbon nanomaterial in the slurry of Comparative Example 1 was equal to the total amount of the second carbon nanomaterial and the hydrophobically modified second carbon nanomaterial in the slurry of Example 1.

[0095] The gas diffusion layer obtained in this comparative example is denoted as gas diffusion layer B1 in the present invention.

[0096] Comparative Example 2:

[0097] The gas diffusion layer is prepared by a method substantially the same as that in Example 1; the difference between the preparation process and that in Example 1 is that a portion of the first carbon nanomaterial is hydrophobically modified instead of being hydrophilically modified, and a portion of the second carbon nanomaterial is hydrophilically modified instead of being hydrophobic.

[0098] The carbon material mixture of Comparative Example 2 includes a first carbon nanomaterial, a hydrophobically modified first carbon nanomaterial, a second carbon nanomaterial, and a hydrophilically modified second carbon nanomaterial, which are mixed to form a carbon material mixture. Among them, the mass content of the first carbon nanomaterial in the carbon material mixture of Comparative Example 2 is the same as the mass content of the first carbon nanomaterial in the carbon material mixture of Example 1; the mass content of the hydrophobically modified first carbon nanomaterial in the carbon material mixture of Comparative Example 2 is the same as the mass content of the hydrophilically modified first carbon nanomaterial in the carbon material mixture of Example 1; the mass content of the second carbon nanomaterial in the carbon material mixture of Comparative Example 2 is the same as the mass content of the second carbon nanomaterial in the carbon material mixture of Example 1; the mass content of the hydrophilically modified second carbon nanomaterial in the carbon material mixture of Comparative Example 2 is the same as the mass content of the hydrophobically modified second carbon nanomaterial in the carbon material mixture of Example 1. The gas diffusion layer obtained by this comparative example is marked as gas diffusion layer B2 in the present invention.

[0099] The gas diffusion layers prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were prepared into membrane electrodes and polarization curves were tested. The results are as follows: Figure 5 See Figure 5 At a higher current density (2500mA / cm 2 ), the cell voltages of the membrane electrodes formed by the gas diffusion layers prepared in Example 1 and Example 2 reached 0.543V and 0.48V, respectively, which were significantly improved compared to less than 0.4V of Comparative Example 1 and Comparative Example 2. This shows that the performance of the prepared gas diffusion layer can be significantly improved by modifying part of the carbon material with a larger particle size to be hydrophilic and part of the carbon material with a smaller particle size to be hydrophobic.

Claims

1. A method for preparing a gas diffusion layer having a hydrophilic and hydrophobic transmission channel, characterized in that: include: Step S1, mixing a first carbon nanomaterial, a hydrophilically modified first carbon nanomaterial, a second carbon nanomaterial, and a hydrophobically modified second carbon nanomaterial to form a carbon material mixture; the particle size of the first carbon nanomaterial is larger than the particle size of the second carbon nanomaterial; Step S2, mixing the carbon material mixture, the solvent, and the hydrophobic agent to form a slurry; Step S3, forming a coating on the substrate with the slurry, drying and sintering.

2. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The particle size of the first carbon nanomaterial is 30-50 nm; the particle size of the second carbon nanomaterial is 20-40 nm.

3. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The mass percentage of the hydrophilically modified first carbon nanomaterial in the carbon material mixture is 15% to 30%, and the mass percentage of the hydrophobically modified second carbon nanomaterial in the carbon material mixture is 5% to 10%.

4. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The hydrophilically modified first carbon nanomaterial is prepared by the following method: Step S101, dispersing the first carbon nanomaterial in deionized water to obtain a first carbon nanomaterial dispersion; Step S102, adding p-phenylenediamine or p-aminobenzenesulfonic acid and nitric acid to the first carbon nanomaterial dispersion; ultrasonically stirring for 1 to 3 hours to obtain a first carbon nanomaterial pretreatment solution; Step S103, adding nitrate to the first carbon nanomaterial pretreatment solution, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophilically modified first carbon nanomaterial.

5. The method for preparing a gas diffusion layer according to claim 4, characterized in that: In step S102, the mass ratio of p-phenylenediamine to the first carbon nanomaterial is (0.5-1):1000; In step S103, a sodium nitrate aqueous solution is added dropwise to the first carbon nanomaterial pretreatment solution, and then reacted at 50 to 80°C for 10 to 14 hours.

6. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The hydrophobically modified second carbon nanomaterial is prepared by the following method: Step S201, dispersing the second carbon nanomaterial in a mixed solution of pentafluoroaniline and acetonitrile to obtain a second carbon nanomaterial dispersion; Step S202, adding nitrite to the second carbon nanomaterial dispersion, reacting for 1 to 24 hours, filtering, washing and drying to obtain a hydrophobically modified second carbon nanomaterial.

7. The method for preparing a gas diffusion layer according to claim 6, characterized in that: In step S201, a second carbon nanomaterial is dispersed in a mixed solution of pentafluoroaniline and acetonitrile, and stirred under ultrasonic conditions for 1 to 3 hours to obtain a second carbon nanomaterial dispersion; wherein the mass ratio of the second carbon nanomaterial to pentafluoroaniline is 1:(3 to 5); In step S202, amyl nitrite is added to the second carbon nanomaterial dispersion, and then reacted under reflux conditions for 8 to 12 hours; wherein the working concentration of the amyl nitrite is 0.5 to 5 mol / L.

8. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The first carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder; the second carbon nanomaterial is selected from carbon powder, carbon black powder, acetylene black powder, Ketjen black powder, and graphene powder.

9. The method for preparing a gas diffusion layer according to claim 1, characterized in that: In step S2, the solvent is a mixed solvent of water and alcohol; the hydrophobic agent is at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-ethylene copolymer, and polyvinylidene fluoride.

10. A gas diffusion layer, characterized in that: The gas diffusion layer is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A fuel cell gas diffusion layer and a preparation method thereof

    CN109273724A

  • Butadiene styrene rubber-based right-angled civil defense door sealing rubber strip and preparation method thereof

    CN111763363A

  • Microporous layer slurry, gas diffusion layer, fuel cell and preparation method

    CN112820883A

  • Gradient microporous gas diffusion layer of proton exchange membrane fuel cell and preparation method of gradient microporous gas diffusion layer

    CN113241448A

  • Gas diffusion layer, preparation method thereof and fuel cell

    CN115275218A